DIGITAL FINANCE AND FINANCIAL LITERACY: KEY DRIVERS OF MSME SUCCESS IN EMERGING ECONOMIES - Ikhtyar Pratama; Rismawati Rismawati; Imam Pribadi; Muhammad Aqsa; Duriani Duriani, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
This study explores the impact of Financial Technology (Fintech) and Financial Literacy on the financial performance of Micro, Small, and Medium Enterprises (MSMEs) in Palopo City. Amidst the rapid digitalization, fintech emerges as a transformative force, revolutionizing access to financial services and enabling efficient financial management. This research employs a quantitative descriptive analysis method and multiple linear regression to analyze data from 60 MSMEs utilizing fintech solutions. Our findings reveal that both fintech and financial literacy significantly and positively influence the financial performance of MSMEs, collectively explaining 79.1% of the variance in financial performance. Notably, this study introduces a novel perspective by integrating fintech with financial literacy, emphasizing their synergistic effect on MSME sustainability and growth. The research underscores that fintech adoption facilitates seamless transactions, accurate financial record-keeping, and enhanced access to financial resources. Concurrently, financial literacy equips MSME owners with the knowledge to make informed financial decisions, manage resources effectively, and distinguish between personal and business finances. The combined influence of fintech and financial literacy, as demonstrated, offers a comprehensive approach to improving MSME financial performance in emerging economies. This study's novelty lies in its dual focus on fintech and financial literacy, providing actionable insights for policymakers and practitioners aiming to foster sustainable MSME growth in the digital era.